1996
DOI: 10.1074/jbc.271.36.22117
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Kinesin Motor Domains with α- and β-Tubulin Subunits at a Tau-independent Binding Site

Abstract: Interaction of rat kinesin and Drosophila nonclaret disjunctional motor domains with tubulin was studied by a blot overlay assay. Either plus-end or minus-end-directed motor domain binds at the same extent to both alpha- and beta-tubulin subunits, suggesting that kinesin binding is an intrinsic property of each tubulin subunit and that motor directionality cannot be related to a preferential interaction with a given tubulin subunit. Binding features of dimeric versus monomeric rat kinesin heads suggest that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 57 publications
9
125
0
Order By: Relevance
“…75 In vitro, Tau, MAP1B, and MAP2 bind preferentially to tubulins with moderate levels of polyglutamylation (~3 glutamyl units) whereas MAP1A shows optimal affinity for highly modified tubulins (~6 glutamyl units). [76][77][78] As a-tubulin glutamylation is abundant in very young neurons whereas b-tubulin glutamylation increases during post-natal development, 50 glutamylation could control transitions in MAP binding during neuronal development. 78 Lys 40 a-tubulin acetylation may also influence MAP binding as overexpression of HDAC6 delocalized p58, a MAP involved in the association of Golgi membranes with microtubules.…”
Section: Who Are the Interpreters Of The Tubulin Code?mentioning
confidence: 99%
See 1 more Smart Citation
“…75 In vitro, Tau, MAP1B, and MAP2 bind preferentially to tubulins with moderate levels of polyglutamylation (~3 glutamyl units) whereas MAP1A shows optimal affinity for highly modified tubulins (~6 glutamyl units). [76][77][78] As a-tubulin glutamylation is abundant in very young neurons whereas b-tubulin glutamylation increases during post-natal development, 50 glutamylation could control transitions in MAP binding during neuronal development. 78 Lys 40 a-tubulin acetylation may also influence MAP binding as overexpression of HDAC6 delocalized p58, a MAP involved in the association of Golgi membranes with microtubules.…”
Section: Who Are the Interpreters Of The Tubulin Code?mentioning
confidence: 99%
“…91,92 Gel overlay and antibody inhibition experiments have shown that Kinesin-1 also binds preferentially to tubulin containing 3 glutamyl units. 77 To directly examine the influence of PTMs on motors, recent experiments have utilized microtubules lacking specific PTMs due to genetic ablation of either the PTM sites or enzymes. Reed et al showed that loss of a-tubulin acetylation, a-tubulin detyrosination, or b-tubulin polymodifications resulted in decreased binding of Kinesin-1 to microtubules whereas loss of a-tubulin polymodifications had no effect.…”
Section: Who Are the Interpreters Of The Tubulin Code?mentioning
confidence: 99%
“…Western Blot Analysis-One-dimensional and two-dimensional PAGE were carried out as described previously (15,16). Proteins were transferred onto nitrocellulose membranes (Hybond C, Amersham Biosciences) and the blots were saturated in TBS-T buffer (20 mM Tris, pH 7.5, 136.8 mM NaCl, and 0.1% (v/v) Tween 20) containing 5% (w/v) low fat milk.…”
Section: Left Ventricular Tissue Preparation For Use In Proteomic Andmentioning
confidence: 99%
“…The binding affinity of kinesin motors to microtubules in vitro can be affected by the extent of tubulin polyglutamylation (5,24). To investigate whether ␣-tubulin polyglutamylation affects binding of kinesins to microtubules, we analyzed the ability of kinesins to copurify with microtubules isolated from brains of ROSA22 mutant and control mice (Fig.…”
Section: Effects Of ␣-Tubulin Polyglutamylation On Binding Of Motor Pmentioning
confidence: 99%